SERVICES SYSTEM BUY SELL HOUSE ON PT. JASA ABADI USING INTERNET - Fahrurrizaldy Anas; Yuce Yuliani, SKom, MMSI (Jurnal Sistem Informasi, 2001)
Computer is a media that is very liked by everyone, by using computer media we cancommunicate with the entire world using the Internet. To get information we want wecan use the Internet to find sites that we kno w.Usually someone who wants to sell or buy a home, to pair advertising through printmedia such as newspapers and magazines. This is a barrier, placed print ads that canonly be read by people who are in a particular area or region. For the PT. Jasa Abadioffering home buying and selling services via the Internet to market ads to get readand seen from different directions.So someone who wants to sell his house quickly can click on a site that has beensupplied by PT. Jasa Abadi, as well as for buyers who want to get information thatcoveted house, because the PT. Eternal service will help you by providing easy-tosells and ease of buying a home.